Effect of Smoking on Quality of Semen Profiles among Primary Infertility Couple in Bangladesh - Shuvro, Muqsuda Ashraf; Khanam, Shafeya; Haider, Alamgir; Reza, Towrit; Obayed, Trifa; Akter, Selina (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Smoking has different bad effects in the human body. Objective: The purpose of the present study was to effect of smoking on quality of semen profiles among primary infertility couple. Methodology: This case-control study was carried from June 2010 to December 2010 for a period of six months. This study was conducted in the Infertility Centre at Shaheed Suhrawardy Hospital, Dhaka, Bangladesh and also in a selected private clinics of Dhaka City. The male smokers with the age group of more than or equal to 18 years who attended in the outpatient department of Infertility Clinic were selected as case group and nonsmoker male were selected as control group. The semen samples were analyzed in infertility laboratory of Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh. Result: A total number of 200 male were recruited for this study of which 100 cases were in the case group and the rest of 200 cases were in control group. Most of the study population was in the age group of 36 to 40 years which was 44(44.0%) cases and 40(40.0%) cases in case and control groups respectively (p=0.414). The mean with SD of volume of semen was in fewer amounts in case group than control group which was 2.2±0.7 mL and 2.7±0.6 mL respectively (p=0.002). The mean with SD of sperm count of semen was less in case group than control group which was 51.4±20.8/mL and 57.6±17.1/mL respectively (p=0.028). However, the mean with SD of motility of sperm in semen was less in case group than control which was 34.1±10.3 and 62.0±16.7 respectively (p=0.001). Conclusion: In conclusion the volume of semen, sperm count and motility of sperm are significantly associated with the smoking. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):65-68